Projeto de um sistema de backup de energia a partir da geração fotovoltaica para uma unidade básica de saúde - VALENTE, Alan da Silva (2023)
In this work, a case study was carried out in the basic health unit (UBS) São Benedito, located in the rural area of the municipality of Cametá, state of Pará. The health unit is responsible for offering medical and nursing services to the local community, in addition to providing medication, vaccination and treatment for some diseases. The proper functioning of the UBS depends on the supply of electricity, both for carrying out administrative activities and for hospital activities, such as storage of vaccines and medications, preventive exams and sterilization of equipment. The electrical network that supplies the UBS is old and does not meet the needs of the current load, which results in interruptions in the energy supply and, consequently, jeopardizing the services offered by the health unit. The Isolated Photovoltaic System (SFI), commonly called off-grid system, presents itself as an alternative to the supply of electrical energy in remote locations, with difficult access to the electrical network or with unstable energy supply, and, therefore, can contribute to improve the living conditions of populations residing in communities far from urban centers. In order to ensure the continuity of the supply of electricity to priority loads of the UBS, in case of failure in the conventional electrical network, this work proposes to design an energy backup system from photovoltaic generation with storage.